2019
DOI: 10.3390/ijms20174241
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Responses to Viruses and Pathogen Products

Abstract: Mast cells are well accepted as important sentinel cells for host defence against selected pathogens. Their location at mucosal surfaces and ability to mobilize multiple aspects of early immune responses makes them critical contributors to effective immunity in several experimental settings. However, the interactions of mast cells with viruses and pathogen products are complex and can have both detrimental and positive impacts. There is substantial evidence for mast cell mobilization and activation of effector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
142
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(145 citation statements)
references
References 116 publications
(99 reference statements)
0
142
0
3
Order By: Relevance
“…Histamine, the H2R ligand, also regulates bronchoconstriction, airway inflammation, and vasodilation 34 . Mast cells are a major source of histamine and their activation has been reported following viral infections of the respiratory tract [35][36][37] . Therefore, Mast cells may represent an underappreciated source of pro-inflammatory cytokine release in COVID-19 patients 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Histamine, the H2R ligand, also regulates bronchoconstriction, airway inflammation, and vasodilation 34 . Mast cells are a major source of histamine and their activation has been reported following viral infections of the respiratory tract [35][36][37] . Therefore, Mast cells may represent an underappreciated source of pro-inflammatory cytokine release in COVID-19 patients 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For several decades mast cells were considered to play mainly proinflammatory roles in several allergic disorders, such as bronchial asthma [2][3][4]122], allergic rhinitis [5], urticaria [6,7], food allergy [8,9], anaphylaxis [10,11], atopic dermatitis [12], and angioedema [13]. During the last years, it became evident that mast cells represent an important cell during bacterial [26,27,29], fungal [29], viral [25,29], and helminth infections [30,31]. Elegant studies have demonstrated that mast cell-derived mediators can play protective roles against several venoms [114,115].…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, it was demonstrated that mast cells can also produce different proangiogenic [16][17][18] and lymphangiogenic factors [19,20], suggesting that they may actually play a role in tumor initiation and growth [21][22][23][24]. Moreover, these cells can be activated by different viral [25,26] and bacterial proteins [27,28] and thereby represent a potentially important cell during microbial infections. Therefore, the spectrum of diseases in which mast cells and their mediators have been implicated has extended to include bacterial, fungal, viral, and helminth infections [26,[29][30][31]; several diseases of the cardiovascular [14,32,33] and gastrointestinal systems [34][35][36]; and the joints [37,38].…”
mentioning
confidence: 99%
See 2 more Smart Citations